Stigma toward People with Schizophrenia among Employees in Wangaya Hospital - Oky Ozika Dewi; I Putu Belly Sutrisna; I Gusti Rai Putra Wiguna; Nyoman Widhyalestari Parwatha (Faculty of Medicine, Universitas Airlangga, 2026)
Introduction: One of the most serious mental health issues in Indonesia is stigma. Schizophrenia is a mental illness that carries a lot of stigma. Stigma makes people with schizophrenia distinct and undervalued, so it can have a negative influence on sufferers. The purpose of this study is to describe stigma toward people with schizophrenia among employees in Wangaya Hospital. Methods: The study used a quantitative descriptive method and was conducted at Wangaya Hospital in February and March of 2023. The collected samples were 91 respondents using simple random sampling. A sociodemographic questionnaire and Community Attitudes toward Mental Illness (CAMI) scale were used to collect data. The data was then analyzed using the software SPSS version 25. Results: The majority of respondents (38.5%) were between the ages of 26 and 35, female (84.6%), had a bachelor’s degree (54.9%), worked as paramedics (42.9%), were Hindus (95.6%), married (78%), and had undergone mental health/disorder education (60.4%). More respondents show contra criteria to the subscales of authoritarianism (51.6%), benevolence (52.7%), social restrictiveness (52.7%), and community mental health ideology (51.7%). Conclusion: There is stigma discovered among employees in Wangaya Hospital, so it requires an intervention measure to alleviate the stigma toward people with schizophrenia.